Agricultural diversity and food security in the South of Algeria - Rachid, Houichiti; Samia, Bissati; Boualem, Bouammar (Journal of Aridland Agriculture, 2017)
In this article we try to introduce the different agriculture forms adapted in the Province of Ghardaïa southern Algeria and to identify their development perspectives in the purpose of reaching food security.Â The research work was based on survey at the agricultural area of the region let us know four agriculture forms. First,Â oldÂ palm for subsistence, new palm agricultureÂ for business vocation,Â then pre-oasisÂ agricultureÂ known by itsÂ market garden and livestock farming andÂ Â the fourth one isÂ extra-oasisÂ featured byÂ large scale farming. In addition to their different way of exploitation, the agricultural form present different potentialities in the development and food security.Â Â Â Key words: Agriculture, Development, Food security, Oasis, Palmary.